Isolation of Escherichia coli bacteriophages from Domestic Wastewater in Tangerang Selatan - Amelia, Puteri; Adila, Ersa Fiki; Novitri, Suci Ahda; Janatiningrum, Isra (JSFK (Jurnal Sains Farmasi & Klinis), 2023)
In recent years, there has been a continuous increase in the prevalence of antibiotic resistance among bacteria responsible for infectious diseases. Several studies have shown that the occurrence of the COVID-19 pandemic is a major factor contributing to this rapid increase. To overcome this challenge, one promising approach is the use of bacteriophages as a treatment option. Therefore, this study aims to isolate E. coli lytic bacteriophages as an alternative antibiotic for treating secondary bacterial infections of COVID-19. Isolation of bacteriophages was carried out using the plaque assay method with double layer agar technique. The isolate obtained was purified and tested for effectiveness in lysing E. coli ATCC 25922 bacterial cells. The results showed that E. coli had resistance to antibiotics, such as Amoxicillin, Clindamycin, Ciprofloxacin, Azithromycin, and Trimethoprim/sulfamethoxazole. BEB1 isolate obtained from domestic waste had activity in inhibiting the growth of the test bacteria with an effectiveness of 72% at the 25th hour. Based on these findings, it had the potential to be developed as an alternative antibiotic agent to overcome infectious diseases caused by E. coli ATCC 25922.